PENGARUH HARGA, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR “BEAT” PADA MAHASISWA - Prakasa, Raja Rio; Berampu, Lailan Tawila; Alvionita, Agnes (Universitas HKBP Nommensen, 2025)
This study aims to determine the price, product quality, and trust in the decision to purchase a Beat motorcycle among students of the Faculty of Economics and Business, University of Riau. The population of this study was 135 students of the Faculty of Economics and Business. The sampling technique used a non-probability sampling technique. The data collection technique used a questionnaire that was analyzed using multiple linear regression. The results of the study indicate that price, product quality and trust have an influence on the decision to purchase a BeAT motorcycle. Price has a significant effect on the decision to purchase a BeAT motorcycle as evidenced by the t-count value of 3.470> t-table 1.978 or sig of 0.001 <0.05. Product quality has a significant effect on the decision to purchase a BeAT motorcycle as evidenced by the t-count value of 4.075> t-table 1.978 or sig of 0.000 <0.05. Trust has a significant effect on the decision to purchase a BeAT motorcycle as evidenced by the t-count value of 5.377> t-table 1.978 or sig of 0.000 <0.05